Negative electrode for electrochemical device and electrochemical device

By forming a two-layer coating structure of lithium carbonate and solid electrolyte on the negative electrode material layer of the lithium ion electrochemical device, the problem of excessive SEI coating increases internal resistance, and the performance improvement of the electrochemical device is achieved.

CN115380346BActive Publication Date: 2025-02-18PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180022456.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-03-26
Filing Date
2021-03-25
Publication Date
2025-02-18
Estimated Expiration
2041-03-25

AI Technical Summary

Technical Problem

In the lithium-ion electrochemical device, the solid electrolyte interface coating (SEI coating) formed by the negative electrode material layer during charging and discharging is too thick, resulting in an increase in the internal resistance of the electrochemical device.

Method used

Two-layer coating structure is formed on the surface of the negative electrode material layer. The first layer (the first layer) is composed of lithium carbonate, the second layer (the second layer) is a SEI coating of solid electrolyte, and the second layer is at least partially covering the first The thickness of the first layer and the second layer are respectively controlled to be 1 nm or more than 50 nm or less.

Benefits of technology

It effectively suppresses the rise of the internal resistance of the electrochemical device, especially the resistance of the negative electrode, and improves the performance and reliability of the electrochemical device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115380346B_ABST
    Figure CN115380346B_ABST
Patent Text Reader

Abstract

A negative electrode for an electrochemical device comprises a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, wherein the negative electrode material layer comprises a carbon material, and the surface layer of the negative electrode material layer comprises a first layer containing lithium carbonate and a second layer containing a solid electrolyte, wherein at least a portion of the second layer covers at least a portion of the surface of the carbon material via the first layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a negative electrode for an electrochemical device and an electrochemical device. Background Art

[0002] There is known an electrochemical device in which a carbon material that absorbs lithium ions is used as a negative electrode material layer (see Patent Documents 1 to 3).

[0003] Prior art literature

[0004] Patent Literature

[0005] Patent Document 1: Japanese Patent Application Publication No. 2014-123641

[0006] Patent Document 2: International Publication No. 2007 / 88604 Pamphlet

[0007] Patent Document 3: International Publication No. 2012 / 36249 Pamphlet Summary of the invention

[0008] Problem that the invention aims to solve

[0009] In an electrochemical device using lithium ions, a solid electrolyte interface film (SEI film) is formed on the negative electrode material layer during charge and discharge. The SEI film plays an important role in the charge and discharge reaction, but if the SEI film is formed too thick, the internal resistance of the electrochemical device increases.

[0010] Solutions for solving problems

[0011] One aspect of the present invention relates to a negative electrode for an electrochemical device, comprising a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, wherein the negative electrode material layer comprises a carbon material, and the surface layer of the negative electrode material layer comprises: a first layer comprising lithium carbonate, and a second layer comprising a solid electrolyte, wherein at least a portion of the second layer covers at least a portion of the surface of the carbon material via the first layer. The thickness of the first layer is, for example, not less than 1 nm and not more than 50 mm.

[0012] Another aspect of the present invention relates to an electrochemical device comprising: a positive electrode including a positive electrode core material and a positive electrode material layer carried by the positive electrode core material; the above-mentioned negative electrode; a separator interposed between the positive electrode and the negative electrode; and an electrolyte.

[0013] Another aspect of the present invention relates to a method for manufacturing a negative electrode for an electrochemical device, which comprises: a process of preparing a negative electrode, wherein the negative electrode comprises a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, wherein the negative electrode material layer comprises a carbon material; and a process of forming a first layer on the negative electrode material layer, wherein the first layer covers at least a portion of the surface of the carbon material and contains lithium carbonate and has a thickness of greater than 1 nm and less than 50 nm.

[0014] Effects of the Invention

[0015] According to the present invention, it is possible to effectively suppress an increase in the internal resistance (particularly the resistance of the negative electrode) of an electrochemical device.

[0016] The novel features of the present invention are described in the appended claims, but the present invention in both aspects of structure and content together with other objects and features of the present invention will be better understood through the following detailed description with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 It is a longitudinal cross-sectional view showing the structure of an electrochemical device according to one embodiment of the present invention.

[0018] Figure 2 This is a diagram showing a C1s spectrum of a region (first layer) containing lithium carbonate having a thickness of 30 nm in XPS analysis. DETAILED DESCRIPTION

[0019] An electrochemical device negative electrode according to one embodiment of the present invention comprises a negative electrode core material and a negative electrode material layer carried on the negative electrode core material, wherein the negative electrode material layer comprises a carbon material. The surface layer of the negative electrode material layer is composed of a coating formed on the surface of the carbon material. The coating has a first layer and a second layer. At least a portion of the second layer covers at least a portion of the surface of the carbon material via the first layer. That is, at least a portion of the first layer is covered by the second layer. Such a first layer is between the surface of the carbon material and the second layer, and becomes a base layer of the second layer.

[0020] By making at least the first layer contain lithium carbonate, the surface layer of the negative electrode material layer has a region containing lithium carbonate. The region containing lithium carbonate is, for example, a region where the surface layer or coating of lithium carbonate is substantially observed by analysis based on X-ray photoelectron spectroscopy (XPS). It should be noted that the analysis method is not limited to XPS.

[0021] On the other hand, the second layer is a SEI film containing a solid electrolyte. The SEI film is formed, for example, by the reaction of an electrolyte with a negative electrode in an electrochemical device. The electrolyte can pass not only through the second layer but also through the first layer, so the entire surface portion including the first and second layers can also be referred to as an SEI film. In this specification, for convenience, the second layer is referred to as an SEI film to distinguish it from the first layer.

[0022] The region containing lithium carbonate is formed as the first layer of the surface layer of the negative electrode material layer before assembling the electrochemical device. It is believed that in the case where the region containing lithium carbonate is formed in advance in a manner covering at least a portion of the surface of the carbon material, in the electrochemical device assembled using the negative electrode, a homogeneous and appropriate thickness of the second layer (SEI coating) is formed on the surface of the carbon material by subsequent charge and discharge. Therefore, the rise of the internal resistance of the electrochemical device can be reduced. Here, the thickness of the first layer (region containing lithium carbonate) is, for example, more than 1nm, and in the case of expecting a longer-term effect, it can be set to more than 5nm, and in the case of expecting a more reliable effect, it can be set to more than 10nm. However, if the thickness of the region containing lithium carbonate exceeds 50nm, the region containing lithium carbonate itself becomes a resistance component, and the internal resistance of the electrochemical device becomes larger. Therefore, the thickness of the region containing lithium carbonate can be set to less than 50nm, or less than 30nm.

[0023] The thickness of the second layer can be, for example, 1 nm or more, 3 nm or more, and 5 nm or more is sufficient. If the thickness of the second layer exceeds 20 nm, the second layer itself becomes a resistance component, so there is a tendency for the internal resistance of the electrochemical device to increase in the initial stage of the charge and discharge cycle. Therefore, the thickness of the second layer can be set to 20 nm or less, or it can be set to 10 nm or less.

[0024] The ratio of the thickness A of the first layer to the thickness B of the second layer: A / B is preferably 1 or less from the viewpoint of reducing the initial internal resistance. In this case, the thickness of the second layer is preferably 20 nm or less, and may be 10 nm or less. However, from the viewpoint of forming a well-formed second layer, it is desirable that A / B is 0.1 or more, and for example, the A / B ratio may be 0.2 or more.

[0025] The thickness of the first layer and the second layer is measured by analyzing the surface portion of the negative electrode material layer at multiple locations (at least 5 locations) of the negative electrode material layer. Then, the average of the thickness of the first layer or the second layer obtained at multiple locations can be used as the thickness of the first layer or the second layer. It should be noted that the negative electrode material layer provided for the measurement sample can be peeled off from the negative electrode core material. In this case, it is sufficient to analyze the coating formed on the surface of the carbon material near the surface portion constituting the negative electrode material layer. Specifically, from the area of ​​the negative electrode material layer arranged on the opposite side of the surface joined to the negative electrode core material, the carbon material covered by the coating is collected and used for analysis.

[0026] For the XPS analysis of the surface of the negative electrode material layer, for example, in the chamber of an X-ray photoelectron spectrometer, an argon beam is irradiated to the film formed on the surface of the surface or the carbon material, and the change of each spectrum belonging to C1s or O1s electrons relative to the irradiation time is observed and recorded. At this time, from the viewpoint of avoiding analysis errors, the most superficial spectrum of the surface can be ignored. The thickness of the region belonging to the peak of lithium carbonate is stably observed to correspond to the thickness of the region containing lithium carbonate (here, the thickness of the first layer).

[0027] In the case of a negative electrode taken out from an electrochemical device that has been completed and aged or charged and discharged at least once, the surface layer of the negative electrode material layer has an SEI film (i.e., the second layer) containing a solid electrolyte generated in the electrochemical device. The thickness of the region where the peak of the bond possessed by the compound contained in the SEI film is stably observed corresponds to the thickness of the SEI film (i.e., the thickness of the second layer).

[0028] As the compound contained in the SEI film, a compound containing an element that can be a marker of the second layer is selected. The element that can be a marker of the second layer can be, for example, an element (for example, F) contained in the electrolyte and not substantially contained in the first layer. As the compound containing an element that can be a marker of the second layer, for example, LiF can be selected.

[0029] When the second layer contains LiF, a peak of F1s substantially attributable to LiF bonding is observed when the second layer is measured by X-ray photoelectron spectroscopy. In this case, the thickness of the region where the peak attributable to LiF bonding is stably observed corresponds to the thickness of the second layer.

[0030] On the other hand, the first layer generally does not contain LiF, and even when the first layer is measured by X-ray photoelectron spectroscopy, no substantial F1s peak attributable to LiF bonds is observed. Therefore, the thickness of the first layer can be defined as the thickness of the region where no peak attributable to LiF bonds is stably observed.

[0031] The O1s peak belonging to lithium carbonate can also be observed in the SEI film. However, the SEI film generated in the electrochemical device has a composition different from that of the pre-formed region containing lithium carbonate, so the two can be distinguished. For example, in the XPS analysis of the SEI film, the F1s peak belonging to the LiF bond was observed, but the substantial F1s peak belonging to the LiF bond was not observed in the region containing lithium carbonate. In addition, the lithium carbonate contained in the SEI film is trace. It should be noted that as the Li1s peak, peaks such as those derived from compounds such as ROCO2Li and ROLi can be detected.

[0032] When the region containing lithium carbonate is analyzed by XPS, in addition to the first peak of O1s attributed to the C=O bond, a second peak of O1s attributed to the Li-O bond can be observed. It is believed that the region of the coating near the surface of the carbon material contains a small amount of LiOH or Li2O.

[0033] Specifically, when analyzing the first layer of the surface portion constituting the negative electrode material layer in the depth direction, in the order of the distance from the outermost surface of the surface portion becoming deeper, it can be observed that: the first region where the first peak (O1s belonging to the C=O bond) and the second peak (O1s belonging to the Li-O bond) are observed, and the first peak intensity is greater than the second peak intensity; and the second region where the first peak and the second peak are observed, and the second peak intensity is greater than the first peak intensity. In addition, there may also be a third region that is closer than the first region to the outermost surface of the surface portion, and the first peak is observed but the second peak is not observed. The third region is easily observed when the thickness of the region containing lithium carbonate is large.

[0034] It should be noted that the magnitude of the peak intensity can be determined by the peak height from the baseline.

[0035] In the center of the lithium carbonate-containing region in the thickness direction, the C1s peak attributed to the CC bond is generally not substantially observed, or even if observed, the intensity is half or less of the peak attributed to the C═O bond.

[0036] Next, an electrochemical device according to one embodiment of the present invention comprises: a positive electrode, the positive electrode comprising a positive electrode core material and a positive electrode material layer carried on the positive electrode core material; the above-mentioned negative electrode; a separator between the positive electrode and the negative electrode; and an electrolyte. The negative electrode and the positive electrode together with the separator between them constitute an electrode body. For example, the electrode body is formed in the form of a columnar winding body by winding a strip-shaped positive electrode and a negative electrode respectively with a separator therebetween. In addition, the electrode body can also be formed in the form of a laminated body by stacking a plate-shaped positive electrode and a negative electrode respectively with a separator therebetween.

[0037] The positive electrode material layer, for example, contains a conductive polymer as the positive electrode material. As the conductive polymer, for example, polyaniline or its derivatives can be used. In the electrochemical device using lithium ions, it is expected that the electrochemical device in which the positive electrode material layer contains a conductive polymer and the negative electrode material layer contains a carbon material will be used in various fields such as vehicle-mounted applications. For such an electrochemical device, during charging, the lithium ions in the electrolyte are absorbed and stored in the negative electrode, and the anions are adsorbed (doped) in the positive electrode. In addition, during discharge, the lithium ions are released from the negative electrode into the electrolyte, and the anions are detached (dedoped) from the positive electrode into the electrolyte. The conductive polymer is charged and discharged by doping and dedoping of anions, so the reaction resistance is small and high output is easy to achieve.

[0038] However, conductive polymers are organic substances with low heat resistance and can be dissolved in highly polar solvents of electrolytes. For example, sometimes the solvent in the electrolyte is decomposed by side reactions to generate alcohol. Conductive polymers such as polyaniline are easily affected by alcohol. Specifically, the nonaqueous electrolyte decomposes on the negative electrode, and the decomposed product reacts with the water in the nonaqueous electrolyte to generate a trace amount of alcohol. There is the possibility that polyaniline is dissolved by alcohol. On the other hand, when the surface portion of the negative electrode material layer includes the first layer and the second layer, the structural stability of the surface portion is improved, so side reactions can be suppressed and the generation of alcohol can be suppressed. It is speculated that this is because: when the region containing lithium carbonate as the first layer is used as a base layer to form the SEI film as the second layer, the SEI film is densely formed.

[0039] The anions include, for example, fluorine-containing anions. Electrolyte salts having such anions have a high degree of dissociation and can provide an electrolyte solution with a low viscosity. In addition, by including fluorine-containing anions in the electrolyte, the withstand voltage characteristics of the electrochemical device can be improved.

[0040] Next, a method for manufacturing a negative electrode for an electrochemical device according to one embodiment of the present invention comprises: a first step of preparing a negative electrode, wherein the negative electrode comprises a negative electrode core material and a negative electrode material layer supported on the negative electrode core material, wherein the negative electrode material layer comprises a carbon material; and a second step of forming a first layer on the negative electrode material layer, wherein the first layer covers at least a portion of the surface of the carbon material and contains lithium carbonate and has a thickness of greater than 1 nm and less than 50 nm.

[0041] The second step of forming the first layer covering at least a portion of the surface of the carbon material on the negative electrode material layer can be performed by, for example, a vapor phase method, a coating method, transfer, or the like.

[0042] As the gas phase method, chemical vapor deposition, physical vapor deposition, sputtering and the like can be cited. For example, lithium carbonate can be attached to the surface of the negative electrode material layer using a vacuum vapor deposition device. The pressure in the chamber of the device during vapor deposition is, for example, 10 -2 ~10 -5 Pa, the temperature of the lithium carbonate evaporation source can be 400-600°C, and the temperature of the negative electrode material layer can be -20-80°C.

[0043] As a coating method, a solution or dispersion containing lithium carbonate is applied to the surface of the negative electrode using, for example, a micro-gravure coater and dried to form the first layer. The lithium carbonate content in the solution or dispersion is, for example, 0.3 to 2% by mass. When a solution is used, a concentration below the solubility (for example, about 0.9 to 1.3% by mass in the case of an aqueous solution at room temperature) is sufficient.

[0044] Furthermore, a negative electrode can be obtained by performing a third step of forming a second layer containing a solid electrolyte in a manner covering at least a portion of the first layer. The surface layer portion of the obtained negative electrode material layer has a first layer and a second layer. The second layer is formed in a manner that at least a portion of the second layer covers at least a portion (preferably the entirety) of the surface of the carbon material via the first layer (i.e., the first layer is used as a base layer).

[0045] The third step is performed while the negative electrode material layer and the electrolyte are in contact with each other, and thus can also serve as at least a part of the step of pre-doping the negative electrode material layer with lithium ions. As the lithium ion source for pre-doping, for example, metallic lithium may be used.

[0046] The third step, for example, includes the following aging step: after forming an electrochemical device including a lithium ion source, a predetermined charging voltage (e.g., 3.4 to 4.0 V) is applied between the terminals of the positive electrode and the negative electrode for a predetermined time (e.g., 1 to 75 hours) to complete the pre-doping of lithium ions to the negative electrode. Alternatively, the third step includes a step of performing at least one charge and discharge after forming the electrochemical device. Thus, an SEI film (i.e., the second layer) containing a solid electrolyte is formed on the negative electrode material layer.

[0047] The electrochemical device of the present invention includes electrochemical devices such as lithium ion secondary batteries, lithium ion capacitors, and electric double layer capacitors, and is particularly suitable for an electrochemical device intermediate between a lithium ion secondary battery and a lithium ion capacitor using a conductive polymer as a positive electrode material.

[0048] Figure 1 The structure of an electrochemical device 200 according to one embodiment of the present invention is schematically shown. The electrochemical device 200 comprises: an electrode body 100, a non-aqueous electrolyte (not shown), a metal bottomed battery case 210 for accommodating the electrode body 100 and the non-aqueous electrolyte, and a sealing plate 220 for sealing the opening of the battery case 210. A gasket 221 is arranged at the peripheral portion of the sealing plate 220, and the interior of the battery case 210 is sealed by riveting the open end of the battery case 210 to the gasket 221. The positive electrode collector plate 13 having a through hole 13h in the center is welded to the exposed portion 11x of the positive electrode core material. The other end of the tab lead 15 connected to the positive electrode collector plate 13 at one end is connected to the inner surface of the sealing plate 220. Therefore, the sealing plate 220 has a function as an external positive terminal. On the other hand, the negative electrode collector plate 23 is welded to the exposed portion 21x of the negative electrode core material. The negative electrode current collector plate 23 is directly welded to a welding member provided on the inner bottom surface of the battery case 210. Therefore, the battery case 210 functions as an external negative electrode terminal.

[0049] Hereinafter, each component of the electrochemical device according to the embodiment of the present invention will be described in more detail by taking an electrochemical device using a conductive polymer as a positive electrode material and a carbon material as a negative electrode material as an example.

[0050] (Positive electrode core material)

[0051] The positive electrode core material uses a sheet-like metal material. The sheet-like metal material can be a metal foil, a metal porous body, an etched metal, etc. As the metal material, aluminum, aluminum alloy, nickel, titanium, etc. can be used. The thickness of the positive electrode core material is, for example, 10 to 100 μm. A carbon layer can be formed on the positive electrode core material. The carbon layer is between the positive electrode core material and the positive electrode material layer, and has a function of, for example, improving the current collection from the positive electrode material layer to the positive electrode core material.

[0052] (Carbon layer)

[0053] The carbon layer is formed, for example, by evaporating a conductive carbon material on the surface of the positive electrode core material, or forming a coating of a carbon paste containing a conductive carbon material and drying the coating. The carbon paste contains, for example: a conductive carbon material, a polymer material, and water or an organic solvent. The thickness of the carbon layer can be, for example, 1 to 20 μm. Conductive carbon materials can use graphite, hard carbon, soft carbon, carbon black, etc. Among them, carbon black can form a thin carbon layer with excellent conductivity. Fluororesins, acrylic resins, polyvinyl chloride, styrene-butadiene rubber (SBR), etc. can be used as polymer materials.

[0054] (Positive electrode material layer)

[0055] The positive electrode material layer contains a conductive polymer. The positive electrode material layer is formed, for example, by immersing a positive electrode core material having a carbon layer in a reaction solution containing a raw material monomer containing a conductive polymer, and electrolytically polymerizing the raw material monomer in the presence of the positive electrode core material. At this time, the positive electrode core material is used as an anode for electrolytic polymerization, so as to form a positive electrode material layer containing a conductive polymer in a manner covering the carbon layer. The thickness of the positive electrode material layer can be controlled by the electrolysis current density, the polymerization time, etc. The thickness of the positive electrode material layer is, for example, 10 to 300 μm per single side.

[0056] As the conductive polymer, a π-conjugated polymer is preferred. As a π-conjugated polymer, for example, polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, polypyridine or their derivatives can be used. These can be used alone or in combination of two or more. The weight average molecular weight of the conductive polymer is, for example, 1000 to 100000. It should be noted that the derivative of the π-conjugated polymer refers to a polymer having a π-conjugated polymer such as polypyrrole, polythiophene, polyfuran, polyaniline, polythiophene vinylene, polypyridine as a basic skeleton. For example, polythiophene derivatives include poly (3,4-ethylenedioxythiophene) (PEDOT) and the like.

[0057] The positive electrode material layer may also be formed by a method other than electrolytic polymerization. For example, a positive electrode material layer comprising a conductive polymer may be formed by chemical polymerization of a raw material monomer. Alternatively, a pre-synthesized conductive polymer or a dispersion thereof may be used to form the positive electrode material layer.

[0058] The raw material monomer used in the electrolytic polymerization or chemical polymerization is a polymerizable compound that can generate a conductive polymer by polymerization. The raw material monomer may include an oligomer. As the raw material monomer, for example, aniline, pyrrole, thiophene, furan, thiophene vinylene, pyridine or a derivative thereof is used. These may be used alone or in combination of two or more. Among them, aniline is easily grown on the surface of the carbon layer by electrolytic polymerization.

[0059] Electrolytic polymerization or chemical polymerization can be carried out using a reaction solution containing anions (dopants). By doping dopants in π-electron conjugated polymers, excellent conductivity can be exhibited. For example, in chemical polymerization, the positive electrode core material is immersed in a reaction solution containing a dopant, an oxidant and a raw material monomer, and then lifted from the reaction solution and dried. In electrolytic polymerization, the positive electrode core material and the counter electrode are immersed in a reaction solution containing a dopant and a raw material monomer, and the positive electrode core material is used as an anode, and current is allowed to flow between the two.

[0060] Examples of dopants include sulfate ions, nitrate ions, phosphate ions, borate ions, benzenesulfonate ions, naphthalenesulfonate ions, toluenesulfonate ions, and methanesulfonate ions (CF3SO3 - ), perchlorate ion (CkO4 - ), tetrafluoroborate ion (BF4 - ), hexafluorophosphate ion (PF6 - ), fluorosulfate ion (FSO3 - ), bis(fluorosulfonyl)imide ion (N(FSO2)2 - ), bis(trifluoromethanesulfonyl)imide ion (N(CF3SO2)2 - ) etc. These may be used alone or in combination of two or more.

[0061] The dopant may be a polymer ion. Examples of the polymer ion include polyvinyl sulfonic acid, polystyrene sulfonic acid, polyallyl sulfonic acid, polyacrylic acid sulfonic acid, polymethacrylic acid sulfonic acid, poly(2-acrylamide-2-methylpropane sulfonic acid), polyisoprene sulfonic acid, and polyacrylic acid. These may be homopolymers or copolymers of two or more monomers. These may be used alone or in combination of two or more.

[0062] (Positive electrode collector plate)

[0063] The positive electrode collector plate is a roughly disc-shaped metal plate. A through hole is preferably formed in the central portion of the positive electrode collector plate as a passage for the non-aqueous electrolyte. The material of the positive electrode collector plate is, for example, aluminum, aluminum alloy, titanium, stainless steel, etc. The material of the positive electrode collector plate can be the same as the material of the positive electrode core material.

[0064] (Negative electrode core material)

[0065] The negative electrode core material also uses a sheet-like metal material. The sheet-like metal material can be a metal foil, a metal porous body, an etched metal, etc. As the metal material, copper, copper alloy, nickel, stainless steel, etc. can be used. The thickness of the negative electrode core material is smaller than that of the positive electrode core material, for example, 10 to 100 μm.

[0066] (Negative electrode material layer)

[0067] The negative electrode material layer has a carbon material that electrochemically absorbs and releases lithium ions as a negative electrode active material. As the carbon material, graphite, difficult-graphitization carbon (hard carbon), and easy-graphitization carbon (soft carbon) are preferred, and graphite and hard carbon are particularly preferred. Carbon materials and other materials may also be used in combination.

[0068] The negative electrode material layer may contain a conductive agent, a binder, etc. in addition to the negative electrode active material. Examples of the conductive agent include carbon black and carbon fiber. Examples of the binder include fluororesins, acrylic resins, rubber materials, and cellulose derivatives.

[0069] The negative electrode material layer is formed, for example, by mixing the negative electrode active material, the conductive agent, the binder, etc., with a dispersion medium to prepare a negative electrode mixture paste, applying the negative electrode mixture paste to the negative electrode collector, and drying. The thickness of the negative electrode material layer is, for example, 10 to 300 μm per single side.

[0070] Pre-doping lithium ions in the negative electrode material layer in advance. As a result, the potential of the negative electrode is reduced, so the potential difference (i.e., voltage) between the positive electrode and the negative electrode becomes larger, and the energy density of the electrochemical device is improved. Pre-doping of lithium ions into the negative electrode material layer is performed by impregnating metallic lithium with the negative electrode in a non-aqueous electrolyte. Lithium ions dissolve from metallic lithium into the non-aqueous electrolyte and are absorbed and stored in the negative electrode material layer. The amount of pre-doped lithium can be set to, for example, about 50% to 95% of the maximum amount that can be absorbed and stored in the negative electrode material layer.

[0071] (Negative electrode collector plate)

[0072] The negative electrode collector plate is a substantially disc-shaped metal plate. The material of the negative electrode collector plate is, for example, copper, copper alloy, nickel, stainless steel, etc. The material of the negative electrode collector plate can be the same as the material of the negative electrode core material.

[0073] (Spacer)

[0074] As the separator, there can be used nonwoven fabrics made of cellulose fibers, nonwoven fabrics made of glass fibers, microporous films made of polyolefins, woven fabrics, or nonwoven fabrics, etc. The thickness of the separator is, for example, 10 to 300 μm, and preferably 10 to 40 μm.

[0075] (Electrolytes)

[0076] The electrolyte has lithium ion conductivity and includes a lithium salt and a solvent that dissolves the lithium salt. The anions of the lithium salt are reversibly repeatedly doped and dedoped to the positive electrode. The lithium ions from the lithium salt are reversibly stored and released by the negative electrode.

[0077] Examples of lithium salts include LiClO4, LiBF4, LiPF6, LiAlCl4, LiSbF6, LiSCN, LiCF3SO3, LiFSO3, LiCF3CO2, LiAsF6, LiB 10 Cl 10 , LiCl, LiBr, LiI, LiBCl4, LiN(FSO2)2, LiN(CF3SO2)2, etc. These can be used alone or in combination of two or more. Among them, salts containing fluorine anions are preferred. The concentration of lithium salt in the non-aqueous electrolyte in the charged state (charge rate (SOC) 90% to 100%) is, for example, 0.2 to 5 mol / L.

[0078] As the solvent, cyclic carbonates such as ethylene carbonate, propylene carbonate, and butylene carbonate, chain carbonates such as dimethyl carbonate, diethyl carbonate, and ethyl methyl carbonate, aliphatic carboxylates such as methyl formate, methyl acetate, methyl propionate, and ethyl propionate, lactones such as γ-butyrolactone and γ-valerolactone, chain ethers such as 1,2-dimethoxyethane (DME), 1,2-diethoxyethane (DEE), and ethoxymethoxyethane (EME), cyclic ethers such as tetrahydrofuran and 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, acetamide, dimethylformamide, dioxolane, acetonitrile, propionitrile, nitromethane, ethyl glycol dimethyl ether, trimethoxymethane, sulfolane, methyl sulfolane, 1,3-propane sultone, etc. can be used. These can be used alone or in combination of two or more.

[0079] The electrolyte may contain various additives as required. For example, unsaturated carbonates such as vinylene carbonate, vinylethylene carbonate, and divinylethylene carbonate may be added as an additive to form a lithium ion conductive film on the surface of the negative electrode.

[0080] [Example]

[0081] Hereinafter, the present invention will be described in more detail based on Examples, but the present invention is not limited to the Examples.

[0082] (Example 1)

[0083] (1) Preparation of positive electrode

[0084] A carbon layer (2 μm thick) containing carbon black was formed on both sides of an aluminum foil (positive electrode core material) having a thickness of 25 μm. On the other hand, an aniline aqueous solution containing aniline and sulfuric acid was prepared. The positive electrode core material and the counter electrode were immersed in the aniline aqueous solution at 10 mA / cm 2 The electrolytic polymerization was carried out for 20 minutes at a current density of 1.5 % to make the sulfuric acid ion (SO4 2- ) is grown on the carbon layer as a positive electrode material layer. At this time, a positive electrode core material exposed portion with a width of 10 mm is formed at the end along the length direction of the positive electrode core material. Next, the conductive polymer doped with sulfate ions is reduced, and the doped sulfate ions are dedoped, and then the positive electrode material layer is thoroughly cleaned and dried. The thickness of the positive electrode material layer is set to 50 μm per single side.

[0085] (2) Preparation of negative electrode

[0086] Prepare a copper foil (negative electrode core material) with a thickness of 10 μm. On the other hand, mix a mixed powder of 97 parts by mass of hard carbon, 1 part by mass of carboxyl cellulose and 2 parts by mass of styrene butadiene rubber with water at a mass ratio of 40:60 to prepare a negative electrode mixture paste. Apply the negative electrode mixture paste to both sides of the negative electrode core material and dry it to form a negative electrode material layer with a thickness of 50 μm. Form a negative electrode core material exposed portion with a width of 10 mm at the end along the length direction of the negative electrode core material.

[0087] Thereafter, a lithium carbonate source was introduced into the chamber of the device, and a first layer containing lithium carbonate was formed on the negative electrode material layer by a gas phase method. The pressure in the chamber was set to 10 -2 pa. The temperature of the negative electrode was set to -10°C. The temperature of the lithium carbonate evaporation source was set to 500°C. The thickness of the first layer was changed as described in Table 1 to obtain negative electrodes A1 to A9 of the embodiment and negative electrode B1 of the comparative example. It should be noted that the negative electrode B1 of comparative example 1 does not form the first layer containing lithium carbonate in the negative electrode material layer.

[0088] [Evaluation 1]

[0089] XPS analysis was performed on the surface of the negative electrode material layer to measure the thickness of the region (first layer) containing lithium carbonate. An X-ray photoelectron spectrometer (trade name: Model 5600, manufactured by ULVAC-PHI, Inc.) was used for the XPS analysis. The measurement conditions are shown below.

[0090] X-ray source: Al-mono (1486.6eV) 14kV / 200W

[0091] Measuring diameter:

[0092] Photoelectron extraction angle: 45°

[0093] Etching conditions: acceleration voltage 3kV, etching rate about 3.1nm / min (SiO2 conversion), grating area 3.1mm×3.4mm

[0094] Figure 2 : This is a diagram showing the C1s spectrum of the first layer of the negative electrode material layer of negative electrode A4 of Example 4 obtained by XPS analysis.

[0095] according to Figure 2 , peaks of C-C bonds, etc., which are presumed to be impurity carbon, can be seen at the outermost surface of the first layer, which decreases sharply near the depth of 1 to 3 nm in the first layer and almost disappears at a depth of 10 to 20 nm. It is presumed that the peaks of C-C bonds, etc., which can be seen in the deep part, are peaks derived from the hard carbon of the active material. On the other hand, peaks attributable to C=O bonds are stably observed from the outermost surface of the first layer to a depth of 30 nm.

[0096] (3) Fabrication of electrode body

[0097] The positive electrode and the negative electrode were wound into a columnar shape through a separator (thickness 35 μm) of cellulose nonwoven fabric to form an electrode body. At this time, the exposed portion of the positive electrode core material protruded from one end face of the wound body, and the exposed portion of the negative electrode core material protruded from the other end face of the electrode body. Disc-shaped positive and negative collector plates were welded to the exposed portion of the positive electrode core material and the exposed portion of the negative electrode core material, respectively.

[0098] (4) Preparation of non-aqueous electrolyte

[0099] A solvent was prepared by adding 0.2% by mass of vinylene carbonate to a mixture of propylene carbonate and dimethyl carbonate in a volume ratio of 1:1. LiPF6 as a lithium salt was dissolved in the obtained solvent at a predetermined concentration to prepare a solution having hexafluorophosphate ions (PF6 - ) as a non-aqueous electrolyte anion.

[0100] (5) Assembly of electrochemical device

[0101] The electrode body is placed in a battery case with an opening and a bottom, the tab lead connected to the positive electrode collector plate is connected to the inner surface of the sealing plate, and the negative electrode collector plate is welded to the inner bottom surface of the battery case. After the non-aqueous electrolyte and the metal lithium foil as the pre-doped lithium ion source are placed in the battery case, the opening of the battery case is sealed with the sealing plate, and the battery case is assembled as shown in FIG. Figure 1The electrochemical device as shown. The amount of pre-doped lithium is set in such a way that the negative electrode potential in the non-aqueous electrolyte after pre-doping is 0.2 V or less relative to metallic lithium. The electrochemical devices using the negative electrodes A1 to A9 of the examples are referred to as batteries A1 to A9 of examples 1 to 9. The electrochemical device using the negative electrode B1 of comparative example 1 is referred to as battery B1 of comparative example 1.

[0102] Thereafter, a charging voltage of 3.8 V is applied between the positive and negative terminals, and aging is performed at 60°C for a predetermined time (10 to 80 hours) to complete the pre-doping of lithium ions into the negative electrode. The thickness of the second layer varies depending on the aging temperature and time. Here, the second layer is controlled to be in the range of 5 nm to 25 nm.

[0103] [Evaluation 2]

[0104] XPS analysis was performed on the surface layer portion of the negative electrode material layer of the negative electrode taken out from the electrochemical device in the same manner as described above. As a result, it was confirmed that an SEI film (second layer) having a thickness shown in Table 1 was formed.

[0105] [Evaluation 3]

[0106] <Initial Characteristics>

[0107] Immediately after aging, the electrochemical device was charged at a voltage of 3.8 V, and the electrostatic capacity was obtained. Also, the electrochemical device was discharged from a voltage of 3.8 V for a predetermined time, and the internal resistance (initial DCR) was obtained from the voltage drop at that time.

[0108] <Characteristics after charge and discharge cycles>

[0109] After repeating 100,000 cycles of charge and discharge in the range of 3.8 V to 2.2 V, the electrostatic capacitance and internal resistance (DCR) were similarly determined.

[0110] <Reliability of negative electrode>

[0111] The thickness of the negative electrode material layer was measured before assembling the electrochemical device and after the above-mentioned charge and discharge cycle. It can be said that the smaller the change in the thickness of the negative electrode material layer is, the better the reliability is.

[0112] The results are shown in Table 1.

[0113] [Table 1]

[0114]

[0115] According to the comparison between Examples 1 to 9 and Comparative Example 1, it can be seen that by forming the first layer, the thickness of the second layer can be easily controlled, the initial DCR can be reduced, and an electrochemical device with excellent reliability of the negative electrode can be obtained. In addition, it can be understood that if the thickness of the first layer is not extremely large, the smaller the thickness of the second layer, the lower the initial DCR can be.

[0116] The small change in the thickness of the negative electrode means that the SEI film initially formed exists stably and is less likely to be damaged or regenerated. Therefore, in each example, the capacity retention rate is high and the DCR increase rate is small.

[0117] It should be noted that even if the first layer is only 0.5 nm thick, the capacity retention rate is significantly improved and the DCR increase rate is significantly reduced compared with Comparative Example 1. The results in Table 1 show that a sufficiently significant effect can be obtained when the thickness of the first layer is 1 μm to 5 μm.

[0118] Industrial Applicability

[0119] The electrochemical device according to the present invention is suitable for use in vehicles, for example.

[0120] Description of Reference Numerals

[0121] 100: Electrode body

[0122] 10: Positive electrode

[0123] 11x: Positive electrode core material exposed

[0124] 13: Positive electrode collector plate

[0125] 15: Connector lead

[0126] 20: Negative electrode

[0127] 21x: Negative electrode core material exposed

[0128] 23: Negative electrode collector plate

[0129] 30: Spacer

[0130] 200: Electrochemical devices

[0131] 210: Battery housing

[0132] 220: Sealing plate

[0133] 221: Gasket

Claims

1. A negative electrode for an electrochemical device, comprising a negative electrode core material and a negative electrode material layer carried on the negative electrode core material, The negative electrode material layer comprises a carbon material, The surface layer of the negative electrode material layer comprises: a first layer containing lithium carbonate and a second layer containing a solid electrolyte. At least a portion of the second layer covers at least a portion of the surface of the carbon material via the first layer. A ratio A / B of a thickness A of the first layer to a thickness B of the second layer is greater than or equal to 0.2 and less than or equal to 1.

2. The negative electrode for an electrochemical device according to claim 1, wherein The second layer contains lithium carbonate, The content of the lithium carbonate contained in the second layer is smaller than the content of the lithium carbonate contained in the first layer.

3. The negative electrode for an electrochemical device according to claim 1, wherein The thickness of the first layer is greater than or equal to 1 nm and less than or equal to 50 nm.

4. The negative electrode for an electrochemical device according to any one of claims 1 to 3, wherein The second layer has a thickness of 5 nm to 15 nm.

5. The negative electrode for an electrochemical device according to any one of claims 1 to 3, wherein When the first layer was measured by X-ray photoelectron spectroscopy, no substantial F1s peak attributable to the LiF bond was observed. When the second layer was measured by X-ray photoelectron spectroscopy, a peak of F1s substantially attributable to LiF bond was observed.

6. An electrochemical device comprising: A positive electrode, the positive electrode comprising a positive electrode core material and a positive electrode material layer supported on the positive electrode core material; The negative electrode according to any one of claims 1 to 5; a separator between the positive electrode and the negative electrode; and Electrolytes.

7. The electrochemical device according to claim 6, wherein: The positive electrode material layer includes a conductive polymer.

8. The electrochemical device according to claim 6, wherein: The electrolyte comprises lithium ions and fluoride-containing anions.

9. A method for manufacturing a negative electrode for an electrochemical device, comprising: A step of preparing a negative electrode, the negative electrode comprising a negative electrode core material and a negative electrode material layer carried on the negative electrode core material, the negative electrode material layer comprising a carbon material; a step of forming a first layer, the first layer covering at least a portion of the surface of the carbon material and containing lithium carbonate and having a thickness of 1 nm to 50 nm; and forming a second layer including a solid electrolyte so as to cover at least a portion of the first layer, A ratio A / B of a thickness A of the first layer to a thickness B of the second layer is greater than or equal to 0.2 and less than or equal to 1.

Citation Information

Patent Citations

  • Electrochemical device

    JP2014123641A

  • Electric storage element having electrode containing conductive polymer

    WO2007088604A1

  • Method for producing electrode plate group unit for lithium-ion capacitor, and lithium-ion capacitor

    WO2012036249A1

  • A negative electrode active material for an electricity storage device and method for manufacturing the same

    CN101140986A

  • Negative pole piece for lithium-ion battery and preparation method of negative pole piece

    CN105742569A